Real-time supplier selection using digital twin technology: an Analytic Hierarchy Process-based optimization approach - Bányai Tóth, Ágota (Advanced Logistic Systems - Theory and Practice, 2024)
Today, the selection of the optimal suppliers plays an increasingly important role in the efficient operation of supply chains. One of the main reasons for this is that the fourth industrial revolution has seen the emergence of increasingly complex supply chains, involving a growing number of suppliers to meet increasingly diversified customer needs. While manufacturing companies use framework contracts to secure the parts needed to meet uncertain customer needs, framework contracts often fix requirements for a fixed future period in the light of past supplier performance. The Fourth Industrial Revolution is enabling the use of a number of new methods and tools to collect real-time data on supply chain operations and to define key performance indicators (KPIs) that show the performance of individual players in the value chain in real time. In this paper, the author proposes a supplier selection method based on analytic hierarchy process (AHP) that is able to determine the optimal suppliers for current component requirements in real time based on real-time information about the state of each player in the supply chain.